I remember your name : examining the effects of individuation training on racial bias in preschoolers - Ng, Xin Ying (Nanyang Technological University, 2020)
The current study explored the effectiveness of a novel individuation training programme in reducing racial bias among 5- to 6-year-old ethnic Chinese preschoolers in Singapore (N = 201). Preschoolers were assessed on their implicit and explicit biases before and after individuation training (Experimental Condition, n = 114) or a filler task (Control Condition, n = 87). Individuation training involved learning to identify Indian males by their unique names and facial features, while the filler task was an unrelated colouring activity of equivalent duration. We obtained three main findings that were consistent with our hypotheses: 1) preschoolers generally display a significant implicit and explicit biases favouring their own race, 2) training preschoolers to individuate other race resulted in significantly greater reductions in implicit racial bias than compared to a filler task, and 3) training preschoolers to individuate other race did not reduce their explicit racial bias to a greater extent than a filler task. Overall, we found support for the effectiveness of other-race individuation training in reducing pro-own-race implicit bias. The bias reduction effect of our individuation training programme was also achieved with a lower resource burden as compared to similar programmes in previous studies, which has practical benefits for use in community settings.